2018
DOI: 10.1002/cbin.11079
|View full text |Cite
|
Sign up to set email alerts
|

Silymarin ameliorates diabetic cardiomyopathy via inhibiting TGF‐β1/Smad signaling

Abstract: Diabetic cardiomyopathy (DCM) is the leading cause of morbidity and mortality in diabetes mellitus (DM) patients. Previous studies have shown that the transforming growth factor-beta 1 (TGF-b1)/Smad signaling pathway plays a key role in the development of myocardial fibrosis in DCM. Silymarin (SMN) is used clinically to treat liver disorders and acts by influencing TGF-b1. However, the possible effects of silymarin on DCM remain to be elucidated. In our study, the DM animal model was induced by streptozotocin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…It has nephroprotective effects in T2DM and can reduce blood glucose levels [982]. Currently, Meng et al [983] showed that silymarin ameliorates diabetic cardiomyopathy through the inhibition of TGF-β1/Smad signaling, suggesting that silymarin could have a potential role in diabetic cardiomyopathy treatment.…”
Section: Phytochemicals With Antidiabetic Potentialmentioning
confidence: 99%
“…It has nephroprotective effects in T2DM and can reduce blood glucose levels [982]. Currently, Meng et al [983] showed that silymarin ameliorates diabetic cardiomyopathy through the inhibition of TGF-β1/Smad signaling, suggesting that silymarin could have a potential role in diabetic cardiomyopathy treatment.…”
Section: Phytochemicals With Antidiabetic Potentialmentioning
confidence: 99%
“…Thus, this study points towards the potential of silymarin in improving diabetic cardiomyopathy by inhibiting TGF-β1/SMAD signaling. Silymarin can be a potential new candidate for the treatment of diabetic cardiomyopathy ( Meng et al, 2019 ).…”
Section: Role Of Tgf-β Signaling In Diabetesmentioning
confidence: 99%
“…T2DM-induced accumulation of extracellular matrix (ECM) proteins in the heart, also known as myocardial fibrosis, is the most marked histopathological change associated with DCM [8,14,15,[80][81][82][83][84]. Myocardial fibrosis leads to structural and functional changes in the heart through collagen deposition, interstitial fibrosis, and perivascular fibrosis [14].…”
Section: Myocardial Fibrosismentioning
confidence: 99%